The effects of visual input and text types on the listening comprehension of EFL students in China - Shaojie, Tan; Abd Samad, Arshad; Ismail, Lilliati (Universiti Putra Malaysia, 2022)
In recent years, there has been an interest in using visual input in multimodal applications for language learning. However, the effects of visual input in listening materials remain to be discussed. Past literature has shown no unified answer to the effects of video input in improving listening comprehension scores. Since there are many proposals for the diversified reform of English teaching methods, it is worth examining whether using traditional audio listening only or using different video inputs can bring more significant benefits to students. The subjects of this study are 30 non-English majors in Chinese universities. This paper applied the quantitative research method, testing students’ performance using different listening visual inputs (content, context, and audio only) and different listening text types (monologue and dialogue). Data were analysed using the two-way repeated measures within groups ANOVA. The interaction effects and the main effect of variables on listening performance were examined to explore the impact of visual input and text types on English listening comprehension. The following conclusions are drawn from the data analysis: (1) The interaction effect shows that video and text types significantly affect students’ listening scores. Videos that contain authentic listening scenes and content elements are beneficial to promote listening comprehension as they support students’ interpretation and understanding of what they hear, and (2) It was noted that grouping students by listening proficiency and examining their cultural background would expand the study in the future.